Cervical cytology screening among low-income, minority adolescents in New York City following the 2009 ACOG guidelines - Tsui, Jennifer (2014)
OBJECTIVES: In December 2009, the American College of Obstetricians and Gynecologists recommended cervical cancer screening begin at age 21 for young women. In this study, we examine receipt of first lifetime Papanicolaou (Pap) test and predictors of over-screening among adolescents within a large urban ambulatory care network. METHODS: We compared the proportion of first lifetime Pap test of adolescents aged 13-20 years between June 2007-November 2009 (n=7700) and December 2009-June 2012 (n=9637) using electronic health records. We employed multivariable regression models to identify demographic and health care factors associated with receiving a first lifetime Pap test at age <21 years in the post-guideline period (over-screening). RESULTS: The proportion of Pap tests declined from 19.3% to 4.2% (p <0.001) between the two periods. Multivariable logistic regression results showed receiving care from gynecology/obstetrics/family planning clinics compared to pediatric clinics, having more clinic encounters, and older age were associated with over-screening in the post-guideline period. CONCLUSIONS: We found that guideline adherence differed by clinic type, insurance status, and health care encounters. In the quickly evolving field of cervical cancer control, it is important to monitor practice trends as they relate to shifts in population-based guidelines, especially in high-risk populations.